WAYS OF POWER EFFICIENCY INCREASE AT DRYING DISPERSABLE PRODUCTS - Burdo O.G.; Kazmiruk Iu.A. (Problems of the Regional Energetics)
In the article questions of power, duration of process and quality production’s quality during drying are discussed. The new approach to modeling of drying and drying equipment is proved. Ways of perfection technologies of drying are analyzed. The mechanism and mathematical model of drying’s process of dispersive staffs by the combined way are presented.